The role of perceived behavioral control in intention to purchase edible bird's nest products - Mohamad Shukri, Nurul Nabilah Huda; Mohd Nawi, Nolila; Abdullah, Amin Mahir; Man, Norsida (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Edible bird’s nests (EBN) is made from solidified saliva from swiftlet (Fuciphagus Aerodramus. EBN is gaining popularity because it is among the most expensive animal products that can be used as health supplements. However, the recent hue in the contamination and adulteration found in EBN become matters of public concern. There are several difficulties and concern found when customers want to purchase EBN products, whether there are genuine and safe to consume, reasonable price, halal certified, and easily find in store. This study used primary data which is structured questionnaire that contains closed-ended questions. Survey was conducted in Klang Valley by using quota sampling (through ethnic-based population: 61.7% for Malays, 20.8% for Chinese, 6.2% for Indian, and 0.9% for other ethnics). The partial least square approach is used for analysis and the results indicate all predictors have strongly significant effects on the perceived behavioral control and leads to positively influence intention to purchase EBN products. In summary, marketers need to consider various decision to motivate buying behavior and aim at reducing customer’s anxiety and difficulties that they encountered in purchasing EBN products.